2019
DOI: 10.3390/cells8020096
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Motor Function Correlates with Neurometabolite and Brain Iron Alterations in Parkinson’s Disease

Abstract: We took advantage of magnetic resonance imaging (MRI) and spectroscopy (MRS) as non-invasive methods to quantify brain iron and neurometabolites, which were analyzed along with other predictors of motor dysfunction in Parkinson’s disease (PD). Tapping hits, tremor amplitude, and the scores derived from part III of the Movement Disorder Society-Sponsored Revision of the Unified Parkinson Disease Rating Scale (MDS-UPDRS3 scores) were determined in 35 male PD patients and 35 controls. The iron-sensitive MRI relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Further, in this work, the ability to separate the high and normal RII iron content patients using QSM data led to the finding that there are in fact group differences in UPDRS-III scores. Similarly, by using R2 ∗ , Pesch et al (2019) found a correlation between iron content and UPDRS-III scores in the SN of 35 PD patients. However, their R2 ∗ measurements were not corrected for age.…”
Section: Discussionmentioning
confidence: 89%
“…Further, in this work, the ability to separate the high and normal RII iron content patients using QSM data led to the finding that there are in fact group differences in UPDRS-III scores. Similarly, by using R2 ∗ , Pesch et al (2019) found a correlation between iron content and UPDRS-III scores in the SN of 35 PD patients. However, their R2 ∗ measurements were not corrected for age.…”
Section: Discussionmentioning
confidence: 89%
“…One article only provided the ranges of the values (22). Four articles did not report values as mean ± SD but as median (range) (10,16,23,24).…”
Section: Articles Reviewmentioning
confidence: 99%
“…In all studies, one or two reviewers blinded to the subject characteristics analyzed the MRI images and drew the contours of the SN (or its different subregions) by hand. As for studies using R2 * MRI, 16 studies drew the SN ROI on anatomical images [T2-weighted images (8,9,11,20,38,43), T2 * -weighted images (10,12,13,17,22,28,29,41), or T1weighted (16,24)], and nine used quantitative maps [six used QSM maps (14,30,31,39,42,44), one used an R2 * map (40), one used a T2 * map (23), one used a T1 map (32), two used magnetization transfer (MT) images, and one of them combined with an anatomical T1-weighted image (33,37)]. The majority of studies assumed that the SN corresponded to the hypointense region on T2-weighted images between the red nucleus and the cerebral peduncle (8,10,20,23,38).…”
Section: Regions Of Interest In the Snmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is of fundamental importance to consider the interplay between metals and peptides. It is well-established that amyloid β and α-synuclein deposits in human brain tissue are associated with metal accumulations, and these metals can affect the aggregation kinetics of amyloidogenic peptides and proteins through the induction of conformational change and/or metal-catalysed oxidation of the protein backbone [11,12,13,14,15,16,17,18,19,20,21,22,23]. It has been postulated that binding of metallic counter-ions neutralises charge repulsion, permitting the formation of more compact and structured conformations, such as those that comprise filamentous Lewy bodies [23].…”
Section: Introductionmentioning
confidence: 99%